Building the Keppel Seghers Tuas WTE plant to support sustainable waste management - BHATTACHARYA, Shantanu (Institutional Knowledge at Singapore Management University, 2022)
Shantanu Bhattacharya, Professor of Operations Management at Singapore Management University (SMU), observed how waste in Singapore was incinerated before it was poured into the country’s only landfill. The government wanted to maximise the country’s limited land resources by using waste-to-energy (WTE) plants that would decrease the volume of waste that was deposited in landfills. Additionally, the heat generated could be used to generate electricity. In 2005, Keppel Seghers was awarded a public-private partnership (PPP) contract to develop the country’s fifth WTE plant. This would be the first incineration plant in Singapore to employ technology from a local company. The PPP structure would allow the government to save on the capital outlay and capitalise on private sector expertise. Keppel Seghers would have to ensure that it would be able to provide sufficient incineration capacity. Bhattacharya supported the waste management strategy but knew the landfill had a limited lifespan. He hoped to study more innovative waste management solutions in the future. This case can be used for undergraduate classes. By analysing the case, students should be able to understand how large infrastructure projects can be undertaken using a PPP structure, appreciate the different forms of PPP structure and how risks are shared among the parties involved and understand the need for more sustainable energy infrastructure.